Multidimensional and Intersectional Gender Identity and Sexual Attraction Patterns of Adolescents for Quantitative Research - Kassis, Wassilis; Aksoy, Dilan; Favre, Céline A.; Artz, Sibylle T.-G. (Frontiers in Psychology, 2021)
To identify and compare gender identity and sexual attraction (GISA) patterns using a Latent Class Analysis (LCA), questionnaire data from a cross-sectional study on social resilience in adolescence was conducted in 2020, using a sample of 785 Swiss seventh grade high school students. Following McCall’s complex intersectionality approach, we applied an intracategorical and intersectional approach to reshape, differentiate, and critique the existing binary, heteronormative GISA categorization. To empirically validate the detected classes according to content, we measured the participants’ psychological characteristics with measures of self-esteem, social competence, symptoms of anxiety and depression, dissociation, social desirability, and emotional styles, and related these measures to the respective GISA gender identity and sexual attraction patterns the LCA detected. The results of our multistep LCA endorsed that heteronormatively binary gender identities are far too simplistic to fully illustrate adolescents’ differences and similarities where gender is concerned. Out of the subsample of n = 785 adolescents (375 identified as “assigned females” and 410 “assigned males”), three significant subgroups of multidimensional GISA patterns emerged for both assigned females and males where differences within the identified GISA groups were larger than those between traditional “boys” and “girls” overall. The LCA demonstrated that the six classes with GISA indicators could be described as “questioning/ LGBTQAI+ (assigned females)”, “cis/heterosexual (assigned females)”, “gender diverse/LGBTQAI+ (assigned females)”, “gender diverse/LGBTQAI+ (assigned males)”, “cis/heterosexual (assigned males)”, “cis-expectation/heterosexual (assigned males)” thus showing that GISA and the psychological state according to gender variance is greater within groups of assigned females and assigned males than between these groups.